Voltammetric Determination of Pyridoxine in Pharmaceutical Samples Using Phosphorus-Doped Copper Oxide Pencil Graphite Electrode - Acikalin, Merve Yalcin; Dokur, Ebrar; Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2024)
A phosphorus-doped copper oxide/pencil graphite electrode (P-doped CuO/PGE) was developed to determine pyridoxine selectively. The phosphorus-doped into the copper has revealed a large number of defects that can provide active sites for the reaction to take place, thus contributing to the improvement of the electrical conductivity of copper oxide. Cyclic voltammetry, electrochemical impedance spectroscopy, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy were employed for the characterization of the P-doped CuO/PGE. Surface morphology was analyzed by field emission scanning electron microscopy. Electrochemical measurements were performed by differential pulse voltammetry, and the limit of detection (LOD) and limit of quantification values for pyridoxine were calculated. The LOD value was 0.33 mu mol L-1 with a linear range of 1.0 and 100 mu mol L-1. The developed sensor showed a remarkable anti-interference effect against interference from ascorbic acid, dopamine, glucose, uric acid, and lactate. Potential interference effects of species that may coexist with pyridoxine in pharmacological samples were also investigated. The applicability of the developed sensor to real samples was examined, and satisfactory recovery values were obtained.
Keywords: pyridoxine; sensor; differential pulse voltammetry; copper nanoparticles; over-oxidation; GLASSY-CARBON ELECTRODE; VITAMIN-B-6; MELATONIN; ASSAY; ACID; Electrochemistry; Materials Science